VICTIMOLOGY ANALYSIS OF LOVE SCAMMING CASES ON FEMALE VICTIMS OF ONLINE MATCHING APPLICATIONS (CASE STUDY ON FEMALE VICTIMS OF ONLINE MATCHING APPLICATIONS) - Amriani, Novia Amriani; Kasmanto Rinaldi (Sisi Lain Realita, 2024)
The phenomenon of love scamming often affects women, especially those using online dating apps. There are many factors that make them vulnerable to such scams. The increasing prevalence of love scamming shows that women are the group most likely to become victims. This study uses a mixed-method approach, involving 30 female respondents who are victims of love scamming and several experts in the fields of digital security and psychology. The results of the study indicate that love scamming among women occurs due to the rapid emotional connections formed through online communication, which makes victims feel close to and trust the perpetrators. Factors that make women vulnerable include low digital literacy, lack of awareness about potential scams, and feelings of loneliness that drive them to seek attention from strangers. According to the victim-triggering theory, women in these cases sometimes unknowingly play a role in accelerating or facilitating the scam by sharing personal information or engaging in more intimate communication. Meanwhile, the routine activity theory explains that victims are more vulnerable to attacks by perpetrators due to opportunities arising from the victim's daily activities related to online dating apps. The conclusion is that love scamming is prevalent among women due to emotional and social dependency factors that make them easier to manipulate. To reduce the impact, digital literacy education, increased awareness of potential scams, and stricter law enforcement against perpetrators are needed.